Top 100 Cited Publications in the Field of Temporomandibular Disorders: A Bibliometric Analysis - Al-Sharaee, Yaser; Al-Moraissi, Essam Ahmed; Christidis, Nikolaos; Galvão, Endi Lanza; Falci, Saulo Gabriel Moreira (Frontiers in Oral Health, 2022)
Background The aim of this bibliometric research was to identify and analyze the top 100 cited publications in the field of temporomandibular disorders (TMD) in order to guide any professional level with interest in this topic by mapping the current trends in the field of TMD. Materials and Methods The Clarivate Analytics' Web of Science database was used to find the top 100 most cited papers in the field of TMD, published from the year 2000 to November 18, 2021, with MeSH terms in the search strategy. Data extracted were ranking, title, main author, institution, publication year, a total of citations, citation average per year, the journal the study was published, journal impact factor, and the number of studies that each journal published. Further, also the percentage of the different study designs, the number of studies regarding a specific area within the field of TMD, and the number of studies per country were also calculated. A ranking of authors was also performed. Results The top cited paper was a study on diagnostic criteria for TMD, with 1,287 citations published in 2014 in the Journal of Oral and Facial Pain and Headache which also had most of the top 100 cited publications. Eighty-one percent of the most cited studies were from the USA and Europe and 33% of the included studies were review articles. Conclusion Taken together, since all papers were considered classic, one can draw the conclusion that researchers in 2000 onward in the field of TMD are interested in (a) diagnostic criteria, (b) TMD symptoms and mainly pain-related symptoms, (c) etiology and risk factors of TMD and mainly bruxism, and (d) treatment of TMD. However, topics such as imaging, occlusion, tissue engineering, and disk displacements are presently not as popular.